Prediction of a Class Variable in Classification Problem Using Fuzzy Inference Method - Devi, S.V.S. Ganga (International Journal of Computer Sciences and Engineering, 2014)
A popular and particularly efficient method for making a decision tree for classification from symbolic data is ID3 algorithm. Revised algorithms for numerical data have been proposed, some of which divide a numerical range into several intervals or fuzzy intervals. Their decision trees, however, are not easy to understand. A new version of ID3 algorithm to generate a understandable fuzzy decision tree using fuzzy sets defined by a user. In this paper, first the fuzzy decision tree is constructed for the given data and then fuzzy reasoning is applied in order to predict the class variable.